Phonon contribution in grazing-incidence fast atom diffraction from insulator surfaces - Frisco, Leandro (2019)
We study the effect of crystal lattice vibrations on grazing-incidence fast atom diffraction (GIFAD) from insulator surfaces. To describe the phonon contribution to GIFAD we introduce a semiquantum method named phonon-surface initial value representation (P-SIVR), which represents the surface with a harmonic-crystal model, while the scattering process is described by means of the surface initial value representation approach, including phonon excitations. Expressions for the partial scattering probabilities involving zero- A nd one-phonon exchange are derived. In particular, the P-SIVR approach for zero-phonon scattering is applied to study the influence of thermal lattice vibrations on GIFAD patterns for Ne/LiF(001) at room temperature. It is found that the thermal lattice fluctuations introduce a polar-angle spread into the projectile distributions, which can affect the relative intensities of the interference maxima, even giving rise to interference subpatterns depending on the incidence conditions. Present results are in agreement with the available experiments.